2005
DOI: 10.1136/jme.2004.008755
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ evaluations of patients’ decisions to refuse oncological treatment

Abstract: Objective:To gain insight into the standards of rationality that physicians use when evaluating patients’ treatment refusals.Design of the study:Qualitative design with indepth interviews.Participants:The study sample included 30 patients with cancer and 16 physicians (oncologists and general practitioners). All patients had refused a recommended oncological treatment.Results:Patients base their treatment refusals mainly on personal values and/or experience. Physicians mainly emphasise the medical perspective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…[29][30][31] Regardless of the setting for nonadherence, the variance between recommended and accepted treatments often stems from the fact that patients tend to make decisions based on values and broader interests whereas physicians tend to emphasize more circumscribed medical goals. 32,33 Informed and Voluntary Refusal of Treatment A patient's intention to leave AMA may trigger physicians and other hospital staff to question the patient's decision-making capacity. 34 One's capacity to make decisions is specific to the decision at hand.…”
mentioning
confidence: 99%
“…[29][30][31] Regardless of the setting for nonadherence, the variance between recommended and accepted treatments often stems from the fact that patients tend to make decisions based on values and broader interests whereas physicians tend to emphasize more circumscribed medical goals. 32,33 Informed and Voluntary Refusal of Treatment A patient's intention to leave AMA may trigger physicians and other hospital staff to question the patient's decision-making capacity. 34 One's capacity to make decisions is specific to the decision at hand.…”
mentioning
confidence: 99%
“…11,12 Reasons for noncompliance with pharmacologic interventions are diverse and include adverse reactions, a fear of long-term effects, the desire for more ''natural'' treatments, and the idea that taking medication is a tacit admission of a diagnosis with which the patient does not agree. 13,14 Americans are seeking complementary and alternative medicine (CAM) treatments for a wide variety conditions, including mental illness. The National Health Interview Survey (NHIS) of 2007 revealed that 38.3% of U.S. adults and 11.8% of children reported using some type of CAM treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Patients mainly refused treatment for reasons of personal values and experiences, something that was difficult to accept for physicians who generally used goal-oriented rationality. Only in the case of noncurativeness did physicians place more emphasis on value-oriented rationality, leading to a better patientphysician relationship (Van Kleffens and Van Leeuwen 2005). Treatment decisions were also the focus in a study of Schildmann et al (2013).…”
Section: Values and Health Carementioning
confidence: 98%
“…Not value conflicts per se, but values explicitly being a basis for decisions are found to play a role in the physician-patient relationship. Van Kleffens and van Leeuwen (2005) interviewed patients and physicians to gain insight into the rationalities of both groups, especially in regard to the patient's refusal of oncological treatment. Patients mainly refused treatment for reasons of personal values and experiences, something that was difficult to accept for physicians who generally used goal-oriented rationality.…”
Section: Values and Health Carementioning
confidence: 99%